Failures related to the measurement of blood pressure among nursing students - Camylla Cavalcante Soares de Freitas; Gabriela de Sousa Martins Melo; Isabelle Katherinne Fernandes Costa; Aline Maino Pergola-Marconato; Manuela Pinto Tibúrcio; Gilson de Vasconcelos Torres (Universidade Federal do Ceará, 2016)
Objective: to identify failures related to the measurement of blood pressure among students of an undergraduate degree in nursing. Methods: this is an analytical, cross-sectional study conducted in skill lab simulated with 76 students, with the application of validated checklist, containing 28 key steps to assess the ability as the measurement of blood pressure in three blocks. To verify the association between the means of each failure, as the blocks by the time of stroke, Kruskal-Wallis, and the correlation Spearman was used. Results: in the three blocks, there were failures in steps: inadequacy in the selection of equipment needed; measuring the patient arm circumference; washing hands. The average failure was lower in the 5th and largest in the 9th period. Conclusion: there were positive correlations ranging from moderate to strong between initial observations (p=0.67) steps of the techniques (p=0.81) and closing remarks (p=0.43) of failures blood pressure period.